1991
DOI: 10.1111/j.1432-1033.1991.tb16469.x
|View full text |Cite
|
Sign up to set email alerts
|

The conformational stability of the redox states of lipoamide dehydrogenase from Azotobacter vinelandii

Abstract: The conformational stability of holo-lipoamide and apo-lipoamide dehydrogenase from Azotohucter vinelandii was studied by thermoinactivation, unfolding and limited proteolysis. The oxidized holoenzyme is thermostable, showing a melting temperature, t, = 80°C. The thermal stability of the holoenzyme drastically decreases upon reduction. Unlike the oxidized and lipoamide two-electron reduced enzyme species, the NADH four-electron reduced enzyme is highly sensitive to unfolding by urea. Loss of energy transfer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In addition, the data collected at 450 nm showed the presence of free FAD; they could be fitted under the assumption that proteinbound FAD was exclusively associated with dimeric human GR. Similar results from fluorescence studies were reported for the Gdn/HCl-induced unfolding of the related flavoenzyme lipoamide dehydrogenase (van Berkel et al, 1991).…”
Section: Resultssupporting
confidence: 86%
“…In addition, the data collected at 450 nm showed the presence of free FAD; they could be fitted under the assumption that proteinbound FAD was exclusively associated with dimeric human GR. Similar results from fluorescence studies were reported for the Gdn/HCl-induced unfolding of the related flavoenzyme lipoamide dehydrogenase (van Berkel et al, 1991).…”
Section: Resultssupporting
confidence: 86%
“…Chemical modification allowed the preparation of monomer, which was reported to retain diaphorase activity (21). In addition, conformational instability of the fully reduced LADH from Azotobacter vinelandii has been reported (22). We have observed inactivation of LADH under reducing conditions, which was favored under more dilute conditions.…”
supporting
confidence: 50%
“…It is important to note that DLS and sedimentation experiments were performed with the native, oxidized form of LADH (i.e. without substrate), whereas diaphorase activity measurements were done under reducing conditions, which is known to stimulate enzyme dissociation (22). The results of sedimentation analysis suggest that the equilibrium between LADH oligomeric forms is pH-sensitive, i.e.…”
Section: Ph-dependent Oligomeric States Of Lipoamide Dehydrogenase 16110mentioning
confidence: 99%
“…A disadvantage of this method is that one needs to find conditions in which the partially unfolded apoprotein is capable of refolding. Circular dichroism spectroscopy [46,118,125–127] and fluorescence spectroscopy [127–129] are useful here to probe the folding behaviour of the protein of interest.…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Then, dimerization occurs as reflected by the lipoamide activity, strongly increased FAD fluorescence and increased hyperchroism of the visible absorption spectrum [151]. For lipoamide dehydrogenase from A. vinelandii , the conformational stability of the monomeric apoprotein was compared with that of the dimeric holoenzyme [128]. Unfolding of the apoenzyme in guanidinium hydrochloride follows a simple two‐state mechanism and is fully reversible.…”
Section: Hydrophobic Interaction Chromatographymentioning
confidence: 99%